Occurrence of Dendrocephalus brasiliensis Pesta, 1921 (Crustacea, Anostraca) in the Caras river, southern Ceara, Brazil - FRANCISCO R.V. FREITA (Anais da Academia Brasileira de Ciências, 2017)
Occurrence of Dendrocephalus brasiliensis Pesta, 1921 (Crustacea, Anostraca) in the Caras river, southern Ceara, Brazil. The specimens were collected in March and April 2014. The new occurrence extends the distribution and update area of occupancy of the species, which is characterized by a specific habitat: temporary lakes.